Diffusion Basis Spectral Imaging Detects Ongoing Brain Inflammation in Virologically Well-Controlled HIV+ Patients. (1st December 2017) - Strain, Jeremy F.; Burdo, Tricia H.; Song, Sheng-Kwei; Sun, Peng; El-Ghazzawy, Omar; Nelson, Brittany; Westerhaus, Elizabeth; Baker, Laurie; Vaida, Florin; Ances, Beau M.
Abstract : Abstract: Inflammation occurs after HIV infection and persists, despite highly active antiretroviral therapy (HAART). Diffusion tensor imaging (DTI) measures HIV-associated white matter changes, but can be confounded by inflammation. Currently, the influence of inflammation on white matter integrity in well-controlled HIV+ patients remains unknown. We used diffusion basis spectral imaging (DBSI)-derived cellularity to isolate restricted water diffusion associated with inflammation separated from the anisotropic diffusion associated with axonal integrity. Ninety-two virologically suppressed HIV+ patients on HAART and 66 HIV uninfected (HIV−) controls underwent neuropsychological performance (NP) testing and neuroimaging. NP tests assessed multiple domains (memory, psychomotor speed, and executive functioning). DTI- and DBSI-derived fractional anisotropy (FA) maps were processed with tract-based spatial statistics for comparison between both groups. Cellularity was assessed regarding age, HIV status, and NP. Within the HIV+ cohort, cellularity was compared with clinical (HAART duration) and laboratory measures of disease (eg, CD4 cell current and nadir). NP was similar for both groups. DTI-derived FA was lower in HIV+ compared with HIV− individuals. By contrast, DBSI-derived FA was similar for both groups. Instead, diffuse increases in cellularity were present in HIV+ individuals. Observed changes in cellularity were significantly associated with age, but not NP, in HIV+ individuals. A trend level association was seen between cellularity and HAART duration. Elevated inflammation, measured by cellularity, persists in virologically well-controlled HIV+ individuals. Widespread cellularity changes occur in younger HIV+ individuals and diminish with aging and duration of HAART. Abstract : Supplemental Digital Content is Available in the Text.